Planar Hall Effect In CrO2 - Keizer, Ruurd S.; Goennenwein, Sebastian T. B.; van Dijk, I.; Klapwijk, Teun M.; Gupta, Arunava (My University, 2006)
We report on anisotropic magnetoresistance (AMR) measurements on epitaxially grown CrO2 thin films patterned into Hall bars. AMR measurements at 4.2K, with the external magnetic field applied in the film plane, reveal both a longitudinal (sheet) and a transverse (planar Hall) resistance. The observation of the planar Hall effect unambiguously demonstrates the presence of two distinct magnetic easy axes in the plane of the CrO2 films. Hence, CrO2 is a biaxial magnetic system, while it is usually considered to be uniaxial.
Keywords: 530